Randomized clinical trial of a digital medication system to enhance adherence in patients with severe mental disorders - Jia Zhou; Qian Zhai; Han Qi; Xiaolei Jin; Cunli Xiao; Wenxiu Li; Junwei Song; Lei Feng; Haibo Wang; Chengcheng Dong; Zibo Yu; Yuan Feng; et al. (npj Digital Medicine)
Abstract To evaluate the effectiveness of a digital medication system in improving adherence among patients with serious mental disorders (SMD), we conducted a cluster-randomized controlled trial across 30 communities in Beijing. Participants, aged 18–65 years, were diagnosed with schizophrenia or bipolar disorder and either received intermittent medication or refused treatment. Recruitment occurred from September 2, 2022, to January 12, 2023. The intervention group received a digital medication system. The control group used an online medication diary. The primary outcome was poor adherence, defined as missing 20% or more of prescribed doses at 12 months. Among 216 recruited patients, 206 completed the study. The intervention group showed significantly higher adherence (84/108 vs. 23/108), with an adjusted risk difference of 52.34% (95% CI: 34.65%–70.03%; P < 0.0001). This trial provides the first robust evidence that the digital medication system can significantly improve medication adherence in patients with SMD. Trial Registration: The trial was registered on the Chinese Clinical Trial Registry (chictr.org.cn) on May 29, 2022 (ChiCTR-ICR-2200060359).